Dendritic cells in cancer immunotherapy: vaccines or autologous transplants? - Kalinski, Pawel (2011)
Dendritic cells (DCs) are the most powerful immunostimulatory cells specialized in the induction and regulation of immune responses. Their properties and the feasibility of their large-scale ex vivo generation led to the application of ex vivo-educated DCs to bypass the dysfunction of endogenous DCs in cancer patients and to induce therapeutic anti-cancer immunity. While multiple paradigms of therapeutic application of DCs reflect their consideration as cancer “vaccines”, numerous features of DC-based vaccination resemble those of autologous transplants, resulting in challenges and opportunities that distinguish them from classical vaccines. In addition to the functional heterogeneity of DC subsets and plasticity of the individual DC types, the unique features of DCs are the kinetic character of their function, limited functional stability, and the possibilitytoimprint in maturing DCs distinct functions relevant for the induction of effective cancer immunity, such as the induction of different effector functions or different homing properties of tumor-specific T cells (delivery of “signal 3” and “signal 4”). These considerations highlight the importance of the application of optimized, potentially patient-specific conditions of ex vivo culture of DCs and their delivery, with the logistic and regulatory implications shared with transplantation and other surgical procedures.